Assessment of elevated concourse as a means of urban expansion - Balane, Ronald S. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Expansion is inevitable in all urban settings. As populations from the countryside gravitate towards the city for employment and as the city's populations also grows, the urban planner is left with the conundrum on how to solve the need for expansion. It left unchecked, the most likely result would be urban sprawl wherein the cheaper peripheral countryside gets bought by developers and turned into subdivisions. Further ramifications result into constant traffic jams due to populations that have moved out to the peripheral using single occupants vehicles adding to the volume of traffic coming in and out of the city. All of these are too familiar in Metro Manila. To solve the swelling traffic, auto-centric development such as road expansions has left us with concrete pavements crisscrossing the city filled with automobiles that pollute the environment. But despite the ugly eventually of such trend, the auto-centric development has given an opportunity that can be explored. The road is a resource that is all around and its underutilized. It occupies only the two-dimensional plane and rarely goes up to the third-dimension in the form of flyovers and elevated railways. It is an agent of transportation that is in need of a makeover.This research has explored developing the vertical void above roads into different developments that can be used as linear expansion for the city's inhabitants. Several policies on building and land use regulations were examined and found conflicting to such development. However, user acceptability is favorable and having such development can actually be beneficial to both the government and its citizen. Elevated Concourse is a new Urban form full of potential for Urban Planning.